A Century of Nonlinearity in the Geosciences. Issue 7 (12th July 2019) - Ghil, Michael
Abstract: This paper provides a thumbnail sketch of the evolution of nonlinear ideas in the mathematics and physics of the geosciences, broadly construed, over the last hundred or so years. It emphasizes the mathematical concepts and methods and outlines simple examples of how they were, are, and maybe will be applied to the solid Earth—that is, the crust, mantle, and core—and its fluid envelopes—that is, the atmosphere and oceans. Plain Language Summary: Nonlinearity has become a buzzword, along with chaos, complexity, fractals, networks, tipping points, turbulence, and other concepts associated with modern science. We outline here what it all means and how it has affected the progress of the geosciences over the past century, mostly over the last six decades or so. Key Points: Nonlinear concepts and methods have greatly expanded the range of problems we can address There is still only a small but increasing number of nonlinear methodologies Prediction is a great test of our mathematical and physical understanding